Non-linear association between serum levels of vitamins A and B12 and accelerated epigenetic aging - Ma, Zhimin; An, Mingxing; Gong, Weiwei; Chen, Xiangyu; Liang, Mingbin; Zhang, Jie; Du, Xiaofu; Lu, Feng; He, Qingfang; Wang, Meng; Zhong, Jieming; Sun, Ce (Frontiers in Nutrition, 2025)
BackgroundSerum vitamins A and B12, as essential micronutrients, play pivotal roles in maintaining physiological homeostasis; however, the association between these vitamins and aging remains unclear. Therefore, this study aims to investigate potential threshold effects of these nutrients on accelerated biological aging using multidimensional DNA methylation biomarkers.MethodsThis study included 2,530 participants with DNA methylation data from the National Health and Nutrition Examination Survey 1999–2000 and 2001–2002. Two age acceleration metrics, derived from epigenetic clocks (PhenoAge and GrimAge), were calculated as the residuals obtained by regressing the epigenetic clock estimates on chronological age. Multivariable logistic regression models were used to analyze the association of vitamins A and B12 with epigenetic clocks. Additionally, generalized additive models and two-piecewise logistic regression were used to explore the non-linear relationships between vitamins A and B12 and epigenetic clocks.ResultsCompared to the first quintile of vitamin A, the odds ratios (ORs) for PhenoAge acceleration in the next four quintiles were 1.24 (0.93–1.65), 1.04 (0.78–1.37), 0.95 (0.71–1.27), and 1.51 (1.13–2.01), respectively. No linear associations were found between vitamin B12 and PhenoAge acceleration, nor between vitamins A and B12 and GrimAge acceleration. However, the generalized additive model showed significant non-linear associations between serum levels of vitamins A and B12 and PhenoAge acceleration, with inflection points at 71.5 and 488.0 pg/mL, respectively. In addition, a non-linear association was observed between serum levels of vitamin A with GrimAge acceleration, with an inflection point at 71.8 μg/dL. Two-piecewise logistic regression also indicated that higher vitamin B12 delayed aging, while higher vitamin A accelerated aging. Sensitivity analyses showed a similar non-linear association between vitamins A and B12 and HannumAge acceleration.ConclusionThis study suggests that higher vitamin A concentrations may be related to an increased risk of aging, while adequate vitamin B12 intake may offer protective benefits against epigenetic changes associated with aging.